Thermal diffusivity of small volume liquids using a converging thermal wave technique - Soltaninejad, Sepideh (2013)
Thermal diffusivity of transparent and large volume liquids has been measured accurately by using pump-probe techniques like thermal lens and hot wire. Therefore, this technique would be rendered useless in the case of opaque and small volume liquids. The probe beam would have very weak transmission in the opaque liquids while small volume liquids would not give an appreciable beam deflection to measure. Since there is always a limited amount of precious liquids for evaluation, it is crucial to have a measuring technique dedicated for small volume transparent and opaque liquids. Such a technique was designed and developed based on a conventional photoflash technique but with an elaborate sample container, which was a small crucible with a thin copper foil base of diameter 10 mm. The liquid filled up about 1 mm height in the crucible during measurement. Thermal waves were induced into the liquid by irradiating the bottom of the container with a camera flash. The heat was generated at the copper base bottom surface subsequent to the radiation absorption before being defused through the base and liquid sample. The temporal temperature of the sample was measured by placing a thermocouple at an appropriate distance in the liquid. The thermal diffusivity was determined by fitting the theoretical temperature to the experimental data. The theoretical temperature was developed based on the hypothesis that the temperature at the point of detection is a product of heat diffusion in the axial and radial directions that depends on the thickness and thermal properties of the bilayer of solid and liquid as well as on the method of heat generation and detection. The whole set up was calibrated by using distilled water. The thermal diffusivity of the distilled water was which was obtained by fitting the theoretical temperature to the experimental data with R-square value of greater than 0.99. Other work has reported values in the range of ( ) . The technique has been used to measure thermal diffusivity of nano-fluids of zinc sulfide, silver, gold and copper nanoparticles suspension in water, and palm oil biodiesel blends. The metal nano-fluids were prepared by using laser ablation while ZnS nano fluid was prepared by using microwave method. The thermal diffusivity of the silver nano-fluids at room temperature increased in the range of ( ) with volume fraction concentration in the range of ⁄ to ⁄ closely matching the results obtained by using thermal lens. The same trend of thermal diffusivity increase with concentration of nanoparticles was also found in the other nano-fluids. The thermal diffusivity of palm-oil-biodiesel blends of B10, B20, B30, B70, and B80 was found in the range of ( ) . Addition of more than 20% biodiesel had no drastic effect in lowering the thermal diffusivity that might help in reducing the fuel volatility due to the increase of the blend flash point.